Two-year clinical outcome of patients with mildly reduced ejection fraction after acute myocardial infarction: insights from the prospective KAMIR-NIH Registry - Jeon, Ho Sung; Lee, Jun-Won; Moon, Jin Sil; Kang, Dae Ryong; Lee, Jung-Hee; Youn, Young Jin; Ahn, Min-Soo; Ahn, Sung Gyun; Yoo, Byung-Su (Frontiers in Cardiovascular Medicine, 2024)
Background: Left ventricular ejection fraction (LVEF) is a crucial prognostic indicator of acute myocardial infarction (AMI). However, studies on the clinical characteristics and prognosis of patients with mildly reduced ejection fraction (EF) after AMI are lacking. Methods: We categorized 6,553 patients with AMI from the Korea Acute Myocardial Infarction Registry-National Institutes of Health (KAMIR-NIH) between November 2011 and December 2015 into three groups based on their EF, assessed by echocardiography during index hospitalization: reduced EF (LVEF ≤40%), mildly reduced EF (LVEF 41–49%), and preserved EF (LVEF ≥50%). The primary outcome was all-cause death within 2 years. The secondary outcomes included myocardial infarction (MI), revascularization, and patient-oriented composite endpoint (POCE) which was defined as composite of all-cause death, any MI, or revascularization. Results: Of the total 6,553 patients, 884 (13.5%) were classified into the reduced EF group, 1,749 (26.7%), into the mildly reduced EF group, and 3,920 (59.8%), into the preserved EF group. Patients with mildly reduced EF exhibited intermediate mortality (reduced EF, 24.7%; mildly reduced EF, 8.3%; preserved EF, 4.6%; p<0.0001), MI (3.9% vs. 2.7% vs. 2.6%; p<0.0046), and POCE (33.0% vs. 15.6% vs. 12.4%; p<0.0001) rates, albeit closer to those of the preserved EF. After adjustment for demographics, risk factors, admission status, and discharge medications, patients with mildly reduced EF showed a lower risk of all-cause death than those with reduced EF (mildly reduced EF group as a reference: HR, 1.74; 95% CI, 1.40–2.18; p<0.001), but it did not differ significantly from those with preserved EF (HR, 0.94; 95% CI, 0.75–1.18; p=0.999). Conclusions: Over a 2-year follow-up period, patients with AMI and mildly reduced EF demonstrated better prognoses than those with reduced EF, but did not differ significantly from those with preserved EF.